Sistem Pelaporan Keamanan Otomatis Menggunakan Arduino Berbasis Android pada Perumahan Ciujung Indah Kragilan - Muhamad Andreas Saputra; Ahmad Rufa’i; Adith Aulia Rahman (CV. Rayyan Dwi Bharata, 2025)
A responsive security system is essential for quickly responding to emergencies in residential areas. This study designed and implemented an ESP32-based security alert system controlled via an Android application at the Ciujung Kragilan Housing Complex. The system replaces conventional methods by utilizing Internet of Things (IoT) technology, where the ESP32 acts as a local access point and web server controlling a siren and audio module. The Android application provides an interface for users to trigger an alert sequence: a 7-second siren followed by a pre-recorded voice announcement based on the incident location. Functional testing showed that all HTTP endpoints (/alarm/on, /alarm/off, /voice/play) were executed successfully with a response time below 500 ms. The system proved effective as a fast and scalable early warning solution and can serve as a foundation for developing more integrated environmental security systems in the future.